Evaluation of science, technology and innovation indicators of Brazil and Spain: a comparative study - Silva, Elaine da; Pomim Valentim, Marta Ligia [UNESP]; Gonzalez, Marta de La Mano (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
Assuming that the science, technology and innovation indicators of a nation serve the function of measuring and monitoring innovative activity, and that knowledge is constituted as a fundamental element in the fostering of innovation, this article aims to analyze science, technology and innovation indicators in Brazil and in Spain regarding processes of production and sharing of scientific knowledge. We carry out a comparative study of the indicators of both countries. To analyze the collected data, we adopt the content analysis research method, more specifically the categorical analysis technique. We observe that only a part of the inferences set by the categories innovation culture valuing knowledge, integrated action of innovation systems agents and knowledge production within the innovation systems is present in the Brazilian and Spanish indicators. Among the variables associated with the set of indicators from both countries, we do not remark any issues concerning the following categories: systematization of knowledge in the context of innovation systems, flows of knowledge in the scope of innovation systems, and appropriation and use of knowledge in the context of innovation systems. We conclude that science, technology and innovation indicators, both Brazilian and Spanish, could be expanded to cover other aspects related to the production and sharing of scientific knowledge for innovation.
Keywords: Science, technology and innovation; Science. technology and innovation indicators; Scientific knowledge; Production and sharing of scientific knowledge